The Opus Dei of violence in Augusto Matraga - Pereira, João Batista (Acta Scientiarum. Language and Culture, 2015)
The experiences experienced by men in modernity transform literary narratives, thematically and formally, establishing the aim to use allegory as an explanatory stage of that new reality. In the book The Origin of German Tragic Drama, by Walter Benjamin, he conceives allegory as the revelation of a hidden truth that does not represent things just as they are, but provides a version of how they were or might have been. As a reflection of the principles implied in that reading, this paper takes Benjamin’s allegory as an analytical category aiming at identifying the representation of violence in the short story A hora e a vez de Augusto Matraga (The Hour and Turn of Augusto Matraga), by Guimarães Rosa. Our analysis opens a dialogue with the dialectical perspective, in which social-historical conditioning factors contribute to understand Minas Gerais backlands, whose ethos supplies a perception of the world incorporated by Guimarães Rosas’ poetics, widening the view of a violent and enchanting world.